Grace and Christology in the early Church - Fairbairn, Donald (Oxford early Christian studies, 2003)
Donald Fairbairn's persuasive study shows that, despite intense theological controversy, there was in fact a strong consensus in the fifth century about what salvation was and who Christ needed to be in order to save people.